Læreplan og demokrati - Emil Sætra; Janicke Heldal Stray (Nordic Journal of Comparative and International Education, 2019)
After the introduction of The Knowledge Promotion (Kunnskapsløftet) in 2006, different forms of criticism have been leveled against the Norwegian Curriculum. Some main points in the critique have been; that the number and scope of the competence aims is too comprehensive; too little emphasis on democratic education; a lack of connection between the general part of the curriculum and subject-specific curricula. In this article, we examine social studies teachers’ narratives about how they utilize different parts of the curriculum from the perspective of democratic education. That means, in essence, that we explore if and how teachers plan their instruction in order for students to acquire knowledge, skills, and values they can utilize in their role as democratic citizens, in addition to the practical ability to act that students derive from experiencing and practicing democracy both in and outside the classroom. A main argument is that most social studies teachers plan their instruction based on the subject-specific competence aims. The general part of the curriculum, where democratic education is highlighted, does not constitute an articulated part of instruction. Against this background it can be argued, from the perspective of democratic education, that it is problematic if the goal-centered rationality underpinning the competence aims is too dominant for the way teaching is practiced, and that this might prevent students from experiencing and practicing democracy in school.